STRATEGI PEMERINTAH DAERAH KABUPATEN ROKAN HILIR UNTUK MEMPEROLEH DANA ALOKASI UMUM (DAU) TAHUN 2009-2012 - Mahfuz, Lauhin; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research was conducted in Bagansiapiapi Rokan Hilir. This study was done to determine and analyze the Local Government Strategy Rokan Hilir To Acquire General Allocation Fund (GAF) Year 2009-2012. Where the Government of the year 2009-2011 Rokan Hilir not get General Allocation Fund and the Government in 2012 Rokan Hilir back Getting the General Allocation Fund. Rokan Hilir Government through the Department of Revenue is quite long struggle, finally Rokan Hilir accept the General Allocation Fund (GAF) Rp. 286 Billion over the past three years Rokan Hilir not accept the General Allocation Fund (GAF). So from the above problems, the problem can be formulated How Local Government Strategy Rokan Hilir To Acquire General Allocation Fund (GAF) Year 2009-2012?In this study, the authors used a qualitative descriptive approach as a method of problem solving and discovery of data sources. The data required for this study is the primary data directly from the informant research and research findings at the time the study took place. This research data collection techniques are interviewing techniques and documentation techniques. Furthermore, after the data is analyzed by qualitative descriptive technique, which is done by analyzing the data and facts.The results showed that the Government Strategy for Obtaining Rokan Hilir General Allocation Fund Year 2009-2012 with 3 (three) points Strategy won the general allocation fund. The first: Improving Planning consisting of Local Government, Regional Infrastructure and Social Affairs, Culture, and Religion. The second: Improving Performance (Regional Development) consisting of Attraction Development, Education, Health and HR (Human Resources) and Agriculture and estates. The third: Main - Informal lobby consisting of Main Facilitated by the Provincial Government of Riau, Riau and Figures Facilitated Main Lobby Jump To Related officials in Jakarta.Keywords: Strategy, Government Rokan Hilir, General Allocation Fund (GAF)